HPLC Method Determination of Isoliquiritin Apioside and Isoliquiritin in Rat Plasma for Application in Pharmacokinetic Study after an Oral Administration of Zhigancao Extract. (24th December 2012) - Yang, Yan-yun; Xu, Liang; Hao, Song-yao; Li, Yan; Zhang, Zhen-Qiu
Abstract : A sensitive HPLC method was developed for the quantitative determination of isoliquiritin apioside (ILA) and isoliquiritin (IL) in rat plasma. After protein precipitation with acetonitrile, chloroform was used to separate lipid-soluble impurities from the plasma samples and remove acetonitrile. A chromatography was carried out on Diamonsil C18 (150 × 4.6  mm; 5  μ m) analytical column, using a mobile phase consisting of water (containing phosphoric acid 0.1%, v/v); acetonitrile (72 : 28, v/v) at a flow rate of 1.0 mL/min. The wavelength-switching technology was performed to determine ILA and IL at 360 nm and wogonoside (internal standard, IS) at 276 nm. The calibration curves of ILA and IL were fairly linear over the concentration ranges of 0.060–3.84  μ g/mL (r = 0.9954 ) and 0.075–4.80  μ g/mL (r = 0.9968 ), respectively. The average extract recoveries of ILA, IL, and IS were all over 80%. The precision and accuracy for all concentrations of quality controls and standards were within 15%. The lower limit of quantification (LLOQ) was 0.060  μ g/mL for ILA and 0.075  μ g/mL for IL. The method was used in pharmacokinetic study after an oral administration of Zhigancao extract to rats.